Efeito terapêutico do extrato de Baccharis anomala em células estreladas hepáticas ativadas - Basso, Bruno de Souza (2017)
The genus Baccharis belongs to the family Asteraceae and has several species widely used in folk medicine and own many compounds of pharmaceutical interest. The aim of this work was to evaluate the cytotoxic, antiproliferative effect and phenotypic reversion of Baccharis anomala extract on activated hepatic stellate cells (HSCs) and identify the compounds present in the extract. In order to evaluate the cytotoxic and antiproliferative effect of the fractionated extract, lactate dehydrogenase (LDH) release and the trypan blue exclusion method were used. The phenotype reversion was evaluated by staining with Oil Red and PPAR-γ expression by RT-PCR. The fractions obtained from the methanolic extract were characterized for their phenolic composition by HPLC. The results showed that two fractions of methanolic extract decreased cell proliferation without increasing LDH release levels. Cell cycle arrest was evaluated using 7-AAD and DAPI staining was used to evaluate indications of apoptosis. Fractions of B.anomala induced cell cycle arrest in G1 phase, while DAPI staining did not reveal cell death by apoptosis. Oil-Red (ORO) staining showed the ability of fractions to induce phenotypic reversion and the evaluation of PPAR-γ mRNA expression was not altered, suggesting that there is an independent PPAR-γ pathway involved. The main components identified in the fractions that presented biological activity were hydroxybenzoic, chlorogenic and coumaric acid. Our study was able to show the antiproliferative effect of methanolic extract fractions of B.anomala, its potential to reverse the activated phenotype of hepatic stellate cells and showed its potential for the treatment of liver fibrosis.